Upaya Mempercepat Proses Involusi Uterus Dengan Pemberian Terapi Komplementer Pijat Oksitosin Pada Ibu Postpartum - liya lugita sari; Taufianie Rossita; Yesi Putri; Syami Yulianti (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Efforts to prevent postpartum hemorrhage can be carried out since the 3rd and 4th stage of labor by administering oxytocin. The hormone oxytocin plays an important role in the process of uterine involution. The involution process will go well if the uterine contractions are strong so that action must be taken to improve uterine contractions. Efforts to control the occurrence of bleeding from the placenta by improving the strong contraction and retraction of myometrial fibers with oxytocin massage. Efforts to maintain uterine contractions through massage to stimulate the release of the hormone oxytocin is an important part of postpartum care. After direct practice, nursing mothers feel stomach contractions, so oxytocin really works and it is hoped that it will speed up the uterine involution process so that bleeding does not occur. Oxotocin massage is very important to speed up the process of uterine involution. So postpartum mothers really need to know the benefits of oxytocin massage for the mother's own health, so that postpartum mothers want to do oxytocin massage. In this community service activity, the lecturers and their students try to contribute their knowledge and experience about complementary techniques, especially